Perception of the organizational mission accomplishment and individual performance in a brazilian public company - Araujo, Uerlei Valdomiro (2019)
This article addresses the individual performance and the perception of the accomplishment of the organizational mission by the workers of a Brazilian state-owned company. It is a descriptive-exploratory study with the application of a survey using the Likert Scale to measure the degree of agreement with the proposed statements. Based on a study already conducted in 2017 with the United States federal public agencies by Lim, Wang, and Lee, this article proposes clarification on the impact of people management practices such as recruitment and selection, training, evaluation and reward, in the perception of the accomplishment of the organizational mission by the Brazilian public workers and what the reflexes in the individual performance. This study has positive implications for public managers in Brazil, because it has a singular look at the characteristics of the Brazilian public service, focusing on the strategic management of human resources and performance management. For the analysis of the data collected, we used a quantitative method of multiple linear regression, documentary research, direct observation and a literature review on the proposed theme.